2012
DOI: 10.1117/1.jmm.11.2.021117
|View full text |Cite
|
Sign up to set email alerts
|

Debris transport analysis at the intermediate focus of an extreme ultraviolet light source

Abstract: As extreme ultraviolet light lithography matures, critical deficits in the technology are being resolved. Research has largely focused on solving the debris issue caused by using warm (Te ∼ 30 eV) and dense (n e ∼ 10 20 cm −3) plasma to create 13.5-nm light. This research has been largely focused on the mitigation of the debris between the plasma and the collector optics. The next step of debris mitigation is investigated, namely the effect of debris mitigation on the transport of undesired contaminants to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Of importance to this study, Harilal found the binary collision approximation code Stopping Range in Matter (SRIM) [12] to under predict the stopping ability of hydrogen buffer gas. Several studies were done looking at the effects of buffer gas on debris transport in a Z-pinch style EUV source which supported the hypothesis of self-similar plasma expansion as the primary mechanism for ion acceleration [8,13]. The first stopping cross sections and collision cross sections were reported in articles by Bleiner [14] and Wu [15].…”
Section: Introductionmentioning
confidence: 93%
“…Of importance to this study, Harilal found the binary collision approximation code Stopping Range in Matter (SRIM) [12] to under predict the stopping ability of hydrogen buffer gas. Several studies were done looking at the effects of buffer gas on debris transport in a Z-pinch style EUV source which supported the hypothesis of self-similar plasma expansion as the primary mechanism for ion acceleration [8,13]. The first stopping cross sections and collision cross sections were reported in articles by Bleiner [14] and Wu [15].…”
Section: Introductionmentioning
confidence: 93%